2019
DOI: 10.1002/jcb.28775
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA H19 promotes chemotherapy resistance in choriocarcinoma cells

Abstract: Choriocarcinoma (CC) is a trophoblast tumor prone to early distant organ metastases. At present, the main treatment for CC is chemotherapy, but chemotherapy resistance readily occurs and leads to treatment failure. H19 is a long noncoding RNA, and its abnormal expression has been found in various tumors, including CC. H19 is also considered to be related to the drug resistance mechanism of the same cancers. To investigate the role of H19 in drug‐resistant CC cells, the following experiments were designed. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
(52 reference statements)
1
16
0
Order By: Relevance
“…Our data show that HORAS5 overexpression increases cabazitaxel resistance via regulation of apoptotic signals. This is consistent with previous studies implicating lncRNAs as regulators of cell apoptosis [63,64] and as mediators of drug resistance [65,66]. In AR + PCa cell, HORAS5 acts mainly by stabilising the AR mRNA, thereby activating AR-target genes, such as the oncogenic KIAA0101 [22].…”
Section: Discussionsupporting
confidence: 92%
“…Our data show that HORAS5 overexpression increases cabazitaxel resistance via regulation of apoptotic signals. This is consistent with previous studies implicating lncRNAs as regulators of cell apoptosis [63,64] and as mediators of drug resistance [65,66]. In AR + PCa cell, HORAS5 acts mainly by stabilising the AR mRNA, thereby activating AR-target genes, such as the oncogenic KIAA0101 [22].…”
Section: Discussionsupporting
confidence: 92%
“…In CC, there is an abnormal expression of H19 where it plays an important role in tumor development [ 62 ]. Yu et al investigated the role of H19 in CC cells which are resistant to drugs and demonstrated that H19 , through the regulation of the PI3K/AKT/mTOR pathway, results in drug resistance together with increased proliferative, migratory, and invasive ability of CC cells [ 61 ]. This suggests H19 may be a potential therapeutic target for the treatment of drug-resistant CC.…”
Section: Dysregulated Lncrnas In Choriocarcinomamentioning
confidence: 99%
“…Choriocarcinoma (CC) is an aggressive, malignant trophoblastic neoplasm, either gestational or nongestational in origin [ 1 ]. Although CC is sensitive to chemotherapy, about 20% of patients with drug-resistant CC experience treatment failure and are at increased risk of metastatic lesions, hysterectomy, and decreased fertility [ 2 , 3 ]. Early metastasis and drug resistance in chemotherapy remain a clinical challenge in CC.…”
Section: Introductionmentioning
confidence: 99%